Purple lettuce (Lactuca sativa L.) performance in response to different doses of bovine manure, grown in PET bottles (Research, Society and Development, 2022)
With the growing population awareness about environmental preservation, the use of Polyethylene Terephthalate (PET) bottles were increasingly used for the cultivation of vegetables, especially lettuce. The objective of this research was to evaluate the performance of 'Roxa' lettuce (Lactuca sativa L.) fertilized with different doses of bovine ester and produced in PET bottles. The experiment was carried out at Sítio Almeida, in Lagoca, PB and was prepared for an experiment in a full design (DIC), containing the following treatments with bovine manure: T1% (control) T2: 25%; T3: 50%; T4: 7%, each with five repetitions. After 25 days of transplanting the seedlings were submitted to 7 studies in the cutting state, in sequence, the plant material was packed in paper and included a forced air circulation oven at 65ºC during the tests hours for drying. The best overall performance of the treatments was the use of a dose of 75% of bovine manure. There was no significant effect (0.05) of bovine manure doses on gas exchange of lettuce plants cv of solution doses in Luvissolo. The model of using PET bottles in a horizontal position is not efficient for the uniform expansion of 'Purple' lettuce, since both the main and adventitious roots are concentrated only in the central part of the bottle, thus failing to receive nutrients from the substrate present on the sides of the bottle.